Editorial do n.40 - Almeida, Aline Novais de; Spineli, Patricia Kiss; Dias, Wagner Miranda (Manuscrítica: Revista de Crítica Genética, 2020)
Editorial da Manuscrítica, edição 40, Rascunhos do Contemporâneo I.